Social Entrepreneurship in Bulgaria − Present and Prospect - Georgieva, Mariela (Student Niepełnosprawny. Szkice i Rozprawy, 2021)
The present paper is focused on the development of social entrepreneurship and social enterprises in Bulgaria. The article presents a theoretical analysis of the legislation that regulates the existence of social enterprises in the country. It outlines and describes the main aspects and effect of social enterprises activity at present.